Emotion regulation across the psychosis continuum. (February 2020) - Chapman, Hannah C.; Visser, Katherine F.; Mittal, Vijay A.; Gibb, Brandon E.; Coles, Meredith E.; Strauss, Gregory P.
Abstract: Emotion regulation dysfunction is characteristic of psychotic disorders, but little is known about how the use of specific types of emotion regulation strategies differs across phases of psychotic illness. This information is vital for understanding factors contributing to psychosis vulnerability states and developing targeted treatments. Three studies were conducted to examine emotion regulation across phases of psychosis, which included (a) adolescent community members with psychotic-like experiences (PLEs; n = 262) and adolescents without PLEs (n = 1, 226); (b) adolescents who met clinical high-risk criteria for a prodromal syndrome (n = 29) and healthy controls (n = 29); and (c) outpatients diagnosed with schizophrenia or schizoaffective disorder (SZ; n = 61) and healthy controls (n = 67). In each study, participants completed the Emotion Regulation Questionnaire and measures of psychiatric symptoms and functional outcome. The three psychosis groups did not differ from each other in reported use of suppression; however, there was evidence for a vulnerability-related, dose-dependent decrease in reappraisal. Across each sample, a lower use of reappraisal was associated with poorer clinical outcomes. Findings indicate that emotion regulation abnormalities occur across a continuum of psychosis vulnerability and represent important targets for intervention.